2022
DOI: 10.1002/jev2.12217
|View full text |Cite
|
Sign up to set email alerts
|

Single extracellular vesicle analysis in human amniotic fluid shows evidence of phenotype alterations in preeclampsia

Abstract: Amniotic fluid surrounding the developing fetus is a complex biological fluid rich in metabolically active bio‐factors. The presence of extracellular vesicles (EVs) in amniotic fluid has been mainly related to foetal urine. We here characterized EVs from term amniotic fluid in terms of surface marker expression using different orthogonal techniques. EVs appeared to be a heterogeneous population expressing markers of renal, placental, epithelial and stem cells. Moreover, we compared amniotic fluid EVs from norm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…EVs derived from bone marrow MSCs can induce T cell apoptosis and increase T regulatory: T effector cell ratio ( ( 38 ). EVs derived from AF have previously been shown to modulate lung tissue structure and vascularization ( 6 , 7 ); however, this is the first time AF-EVs have been shown to affect immune cell activity. Together, this data further demonstrates that AF is a promising and novel source for therapeutic EVs and depicts a potential mechanism of action through the ability to alter the T-cell response.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…EVs derived from bone marrow MSCs can induce T cell apoptosis and increase T regulatory: T effector cell ratio ( ( 38 ). EVs derived from AF have previously been shown to modulate lung tissue structure and vascularization ( 6 , 7 ); however, this is the first time AF-EVs have been shown to affect immune cell activity. Together, this data further demonstrates that AF is a promising and novel source for therapeutic EVs and depicts a potential mechanism of action through the ability to alter the T-cell response.…”
Section: Discussionmentioning
confidence: 86%
“…AF is a rich source of EVs that have been characterized to express EV specific tetraspanins CD9, CD63, and CD81, and to carry immune modulatory and anti-inflammatory RNA and protein cargo ( 6 , 7 ). AF-derived EVs (AF-EVs) can regulate angiogenesis and are capable of altering lung tissue structure ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs cargo can be affected by changes in gene expression resulting from environmental cues such as oxygen levels or inflammation. Based on surface marker expression, Gebara et al [ 147 ] found that amniotic fluid-derived EVs showed a heterogeneous origin; vesicles expressed markers of fetal, placental cells, and also mesenchymal and stem cells markers. Investigations on tetraspanin marker expression profiles in individual EVs have evidenced seven subpopulations.…”
Section: Considerations and Challenges In The Researchmentioning
confidence: 99%